Electronic data collection for the analysis of surgical maneuvers on patients submitted to rhinoplasty - Berger, Cezar; Freitas, Renato; Malafaia, Osvaldo; Pinto, José Simão de Paula; Mocellin, Marcos; Macedo, Evaldo; Fagundes, Marina Serrato Coelho (International Archives of Otorhinolaryngology, 2012)
Introduction: In the health field, computerization has become increasingly necessary in professional practice, since it facilitates data recovery and assists in the development of research with greater scientific rigor.Objective: the present work aimed to develop, apply, and validate specific electronic protocols for patients referred for rhinoplasty.Methods: The prospective research had 3 stages: (1) preparation of theoretical data bases; (2) creation of a master protocol using Integrated System of Electronic Protocol (SINPE©); and (3) elaboration, application, and validation of a specific protocol for the nose and sinuses regarding rhinoplasty.Results: After the preparation of the master protocol, which dealt with the entire field of otorhinolaryngology, we idealized a specific protocol containing all matters related to the patient. In particular, the aesthetic and functional nasal complaints referred for surgical treatment (i.e., rhinoplasty) were organized into 6 main hierarchical categories: anamnesis, physical examination, complementary exams, diagnosis, treatment, and outcome. This protocol utilized these categories and their sub-items: finality; access; surgical maneuvers on the nasal dorsum, tip, and base; clinical evolution after 3, 6, and 12 months; revisional surgery; and quantitative and qualitative evaluations.Conclusion: The developed electronic-specific protocol is feasible and important for information registration from patients referred to rhinoplasty.
Keywords: rhinoplasty; medical informatics; database